Augmented Reality Pengenalan Peralatan Tradisional Bali pada Museum Subak Mascetti Berbasis Android - I Gusti Ayu Agung Mas Aristamy; Putu Risanti Iswardani; Ni Ketut Utami Nilawati (LPPM STT Terpadu Nurul Fikri, 2026)
The Android-based Augmented Reality (AR) application for introducing Balinese traditional tools at the Subak Mascetti Museum was developed as an interactive information and educational medium. This research was motivated by limited information dissemination channels, damage to several traditional tools, and the low level of public knowledge about the history and functions of Balinese traditional tools. These conditions have led to the underutilisation of museum collections as cultural learning resources. This study aims to develop an AR application that presents information on traditional tools in a visual, interactive, and easily understandable manner. The method used is Marker-Based Tracking to display ten 3D models of traditional tools in real time, complemented by museum history information, audio explanations, and bilingual features in Indonesian and English. Application effectiveness testing was conducted to evaluate system performance. The results show an effectiveness score of 85.6%, categorised as very effective. Based on these results, it can be concluded that the developed AR application enhances user understanding and has strong potential as an educational medium to support the preservation of Balinese culture and traditional tools at the Subak Mascetti Museum.